THE EFFECT OF THE USE OF DIGITAL STORYTELLING ON BASIC LEARNING RESULTS OF GRAPHIC DESIGN BASIC - Dyan Yuliana; Okta Ayu Wulandari Putri (UIN Ar-Raniry, 2021)
The development of Information and Communication Technology today has grown very rapidly, this is evidenced by the emergence of sophisticated technological equipment that has changed the lifestyle of humans at this time. As a teacher, of course we must be able to adjust the way of educating them according to their way of life in the digital era. Teachers are required to carry out an innovation in the learning process in the classroom, to support the needs needed in implementing active learning in the classroom, there is a need for media that can support the implementation of learning optimally to spur effective communication skills through active learning that integrates information and communication technology. namely Digital Storytelling (digital storytelling) which is a strategy to use a computer application program that combines audio and visual media. This study used a quantitative research approach with the type of pre-experimental designs with the form of one group pretest posttest design. The decision making of hypothesis testing uses the help of the SPSS version 25 program. The hypothesis testing technique uses the paired sample t-test and simple linear regression. The results obtained through the paired sample t-test in SPSS version 25, namely the sig value. (2- tailed) of 0.001. In accordance with the basis of decision making in the paired sample T-test that the sig. (2-tailed) <0.05 or 0.001 <0.05, then H0 is rejected and Ha is accepted. This means that there is a significant difference between the pretest and posttest results. To find out what percentage of this influence is, it is necessary to look for the coefficient of determination (R Square) with a simple linear regression test in SPSS version 25 and it was found that the effect of Digital Storytelling on student learning outcomes is 0.142 or 14.2% which can be concluded that Digital Storytelling has an effect. which is very low on student learning outcomes at SMKN 1 Kendit.